Organizing of a study tour in Europe for Caribbean business people from the cultural industries : summary of proceedings; presented by ACE, International Consultants, Spain - Mora, Taiana (European Union BrusselsBE, 2012)
Reports on the study tour to the EU for 22 companies in the cultural industry (music, audiovisual and fashion), financed by ACP Bizclim and Caribbean Export.